Participation of locus coeruleus in breathing control in female rats - de Carvalho, Débora [UNESP]; Patrone, Luis Gustavo A. [UNESP]; Marques, Danuzia A. [UNESP]; Vicente, Mariane C. [UNESP]; Szawka, Raphael E.; Anselmo-Franci, Janete A.; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Elsevier, 2017)
Several evidences indicate that the locus coeruleus (LC) is involved in central chemoreception responding to CO2/pH and displaying a high percentage of chemosensitive neurons (>80%). However, there are no studies about the LC-mediated hypercapnic ventilation performed in females. Therefore, we assessed the role of noradrenergic LC neurons in non-ovariectomized (NOVX), ovariectomized (OVX) and estradiol (E2)-treated ovariectomized (OVX + E2) rats in respiratory response to hypercapnia, using a 6-hydroxydopamine (6-OHDA) – lesion model. A reduction in the number of tyrosine hydroxylase (TH) immunoreactive neurons (51–90% in 3 animals of NOVX group, 20–42% of lesion in 5 animals of NOVX females, 61.3% for OVX and 62.6% for OVX + E2 group) was observed seven days after microinjection of 6-OHDA in the LC. The chemical lesion of the LC resulted in decreased respiratory frequency under normocapnic conditions in OVX and OVX + E2 group. Hypercapnia increased ventilation in all groups as consequence of increases in respiratory frequency (fR) and tidal volume (VT). Nevertheless, the hypercapnic ventilatory response was significantly decreased in 6-OHDA-NOVX > 50% rats compared with SHAM-NOVX group and with females that had 20–42% of LC lesion. In OVX and OVX + E2 lesioned groups, no difference in CO2 ventilatory response was observed when compared to SHAM-OVX and SHAM-OVX + E2 groups, respectively. Neither basal body temperature (Tb) nor Tb reduction in response to hypercapnia were affected by E2 treatment, ovariectomy or LC lesion. Thus, our data show that LC noradrenergic neurons seem to exert an excitatory role on the hypercapnic ventilatory response in female rats, as evidenced by the results in NOVX animals with LC lesioned more than 50%; however, this modulation is not observed in OVX and OVX + E2 rats. In addition, LC noradrenergic neurons of OVX females seem to provide a tonic excitatory drive to maintain breathing frequency in normocapnia, and this response may not to be functionally influenced by E2.
Keywords: A6 group; Breathing; CO2; Estradiol; Noradrenaline